FREQUENCY AND SEVERITY OF LIVER INVOLVEMENT IN HYPERTENSIVE DISORDERS OF PREGNANCY - OLIVEIRA,Jade Castro de (2022)
ABSTRACT Background: Pre-eclampsia (PE) and eclampsia (E) are among the leading causes of maternal and fetal morbidity and mortality. Both are associated with an evolving spectrum of liver disorders. Objective: The aim of this study was to evaluate the frequency and severity of liver involvement in pregnant women admitted to an intensive care unit with PE/E and to assess its influence on adverse maternal and fetal outcomes. Methods: All subjects, hospitalized between January 2012 and March 2019, were retrospectively evaluated for clinical and biochemical liver-related abnormalities and their frequencies were subsequently correlated with maternal-fetal outcomes. Results: A total of 210 women (mean age 31±6.4 years, mean gestational age 33.8±4.1 weeks) with PE/E were included in the study. Most of them had severe hypertension (n=184) and symptoms of abdominal pain (48%) and headache (40%). Liver enzymes abnormalities were seen in 49% of the subjects, usually less than five times the upper limit of normal. Subcapsular hemorrhage and spontaneous hepatic rupture were identified in one woman who died. No patient had definitive diagnosis for acute fatty liver of pregnancy, neither acute liver failure. A total of 62% of deliveries occurred before 37 weeks. Fetal mortality was observed in 6 (3%) cases. There was no correlation between mean levels of liver enzymes and maternal and fetal outcomes. Conclusion: Biochemical abnormalities of liver enzymes are frequently seen in women with PE/E, but outside the spectrum of HELLP syndrome, they are not associated with adverse maternal and fetal outcomes. Liver-related complications are rare but can be life-threatening.